Hope and Distress: A Cross-Country Study Amid the Russian-Ukrainian War - Esbit, Simon; Kaim, Arielle; Kimhi, Shaul; Bankauskaite, Dalia; Baran, Maria; Baran, Tomasz; Cosciug, Anatolie; Eshel, Yohannan; Dumbadze, Salome; Gabashvili, Manana; Jiglau, George; Kaniasty, Krzysztof; et al. (Stress and health, 2025)
Conflict deeply affects human experiences, frequently testing individual resilience to its breaking point and leaving enduring psychological and societal wounds. The current conflict in Ukraine, initiated by Russia's invasion in 2022, illustrates this phenomenon by altering regional relationships and triggering a major humanitarian crisis marked by extensive displacement, loss of life, and emotional turmoil. This study explores the factors influencing hope and distress in Ukraine alongside six nearby European countries during the ongoing conflict. A cross-sectional survey collected data primarily via internet panel samples from the Czech Republic, Georgia, Lithuania, Poland, Romania, Slovakia, and Ukraine in the second year since the war's initiation. The current study utilised validated instruments, collecting data on levels of hope, distress, individual resilience, community resilience, societal resilience, morale, sense of danger, perceived security threats, and demographic characteristics. Hope and distress levels differ across countries, with Ukraine exhibiting the highest levels of both (3.74 ± 1.02 and 2.89 ± 0.87, respectively). Overall, average scores of hope were higher than average distress levels. Across the regression models for the seven countries, hope showed strong associations with individual (between β = 0.089 and β = 0.327) and societal resilience (between β = 0.206 and β = 0.514), while morale (between β = -0.104 and β = -0.479) and individual resilience (between β = -0.077 and β = -0.335) displayed a protective relationship against distress (all β values were significant, p < 0.01). Monitoring hope and distress is crucial during the Russian-Ukrainian war and other adversities, as these factors give insight into the current and future psychological states of affected populations. The results offer valuable information that can guide the development of tailored strategies to enhance hope and buffer distress in war-impacted countries, as well as those experiencing its broader effects. Fostering individual and societal resilience, alongside enhancing morale, may strengthen hope and mitigate distress amid adversity. Developing targeted interventions that address each population's unique needs, as well as their sociocultural and geopolitical contexts can enhance efficacy.
Keywords: Humans; lidé středního věku; Ukrajina; ozbrojené konflikty; Female; mladý dospělý; dospělí; lidé; Armed Conflicts; psychický distres; Resilience, Psychological; Stress, Psychological; Adult; psychická odolnost; ženské pohlaví; Male; Middle Aged; naděje; Rusko; psychický stres; Cross-Sectional Studies; Psychological Distress; Russia; Young Adult; Ukraine; mužské pohlaví; průřezové studie; Hope